MANAJEMEN PENDIDIKAN SEKOLAH INKLUSIF DI SEKOLAH DASAR NEGERI GADINGAN KECAMATAN WATES KABUPATEN KULOPROGO (JURNAL ILMIAH TUT WURI HANDAYANI, 2013)
The Management of Inclusive School in SD Negeri Gadingan Wates Kulon Progo Regency. This research used a qualitative approach, where the place of study was in SD Negeri Gadingan, Kulon Progo regency. Researcher served as instruments. Data sources of this study consisted of principal, teachers, and school superintendent. Techniques of data collection used interviews, observation, and documentation. Techniques of data collection in this research were done since the beginning of the study. The findings are analyzed and set forth in meaningful word qualitatively. Test of the data validity used the test of data credibility that fulfills validity, reliability, and objectivity. In addition to using the increased persistence, authors used triangulation credibility test. The Implementation of the management begins with planning that includes eight standard. Implementation of its activities was also referring to the plans that have been made. It stands out from the implementation of the eight standard is the standard process and standard of facilities and infrastructure. For monitoring and evaluation carried out by principals, school supervisors also played an active role.